The Influence of Facebook Social Media on The Spread of Hoax Information on Generation X in Setu Sari Village Cileungsi Subdistrict - Devina Amanda (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Bogor, 2024)
This study aims to determine whether or not the influence of Facebook social media on the dissemination of hoax information to Generation X in one of the villages that the researchers chose as a sample. This research uses a quantitative approach and uses a quantitative descriptive method. This research was carried out in Setu Sari Village, Cileungsi District with 150 respondents as a sample. The data collection technique in this study was through observation, and distributing questionnaires by print out or via the Google Forms link. This study obtained the final results of the t-test, f-test, and simple regression test with a significance value of 0.790. Significance value 0.05, meaning that there is no influence of Facebook social media on the dissemination of hoax information to generation X in Setu Sari Village. The conclusion is that the majority of respondents actively use the Facebook platform as an intermediary for information and entertainment for respondents. This means that from the results of the respondents' answers, the majority of Facebook social media users with the X generation category have advanced in literacy, or it can be interpreted that the X generation in Setu Sari Village currently has good literacy values in receiving information read or from other people so that it can reduce the spread of information. hoaxes that are widely shared on the platform.Keywords: Social Media, Facebook.